2002
DOI: 10.1046/j.1537-2995.2002.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed gel centrifugation test for quantification of RBC‐bound IgG antibodies and their subclasses IgG1 and IgG3: comparison with flow cytometry

Abstract: There is a correlation between the amount of RBC-bound IgG and immune hemolysis. The GCT cards that detect the anti-IgG-gamma-chain may be useful to predict hemolysis in patients with a 2+ or 3+ DAT in the GCT. The diagnostic value of GCT cards for IgG subclass testing should be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 15 publications
(28 reference statements)
4
24
0
4
Order By: Relevance
“…It has been seen that in so called “DAT negative AIHA”, more sensitive techniques such as enzyme linked DAT, flow cytometry (FC) and gel cards can detect IgG or C3d molecules coating the red cells. [89]…”
Section: Introductionmentioning
confidence: 99%
“…It has been seen that in so called “DAT negative AIHA”, more sensitive techniques such as enzyme linked DAT, flow cytometry (FC) and gel cards can detect IgG or C3d molecules coating the red cells. [89]…”
Section: Introductionmentioning
confidence: 99%
“…This difference in results between the two studies may have been due to the increased number of samples in the latter study. Lynen et al [6] found a significant difference in the amount of RBC-bound IgG1 when studying 12 patients with and without severe IHA, but later did not find a significant difference when studying 65 patients with and without IHA [7].…”
Section: Detection and Quantitation Of Globulins Red Blood Cell-boundmentioning
confidence: 98%
“…There is a number of methods used to determine the subclass of IgG antibodies, and FC has been shown to be useful [6,7,15,16]. Garratty et al [16] showed that 12 antibodies that could not be subclassed using a routine capillary method [17] (i.e., all four subclass antisera were nonreactive with the antibody-coated RBCs) could be subclassed using FC.…”
Section: Detection and Quantitation Of Globulins Red Blood Cell-boundmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry (FC) has been previously utilized for antibody detection, including the detection of red cell autoantibodies (4,5), HLA alloantibodies (6,7), platelet crossmatching (8)(9)(10), and other immmunohematological applications (11,12). Recently, FC was also introduced for the screening of antibodies to red cells for automation by Roback et al (3,13).…”
Section: Introductionmentioning
confidence: 99%